The Practice of Contextualizing English Language Activities to Enhance Students’ Learning: the case of technology villages of Hawassa University - Kebebush Kebede Kassa; Nigate, Demekash Asregid (Ethiopian Journal of Education Studies, 2024)
The major objective of this research was to investigate the practice of English language teachers’ practice of contextualizing English language activities to the real life situations of their students. The research tried to answer the basic questions that focus on how classroom teachers adapt activities in English language textbooks to the context of their students, and what factors were hindering teachers’ contextualization of activities. To achieve the purpose and answer the basic questions mixed methods research was used. Data was collected from English language teachers and their students. The data was collected through questionnaire, semi-structured interview, and focus group discussion. The result of the research revealed that teachers’ practice on contextualizing activities is weak. Teachers were using activities in student textbooks without modification. The teachers were not preparing various instructional materials, and were not using various instructions strategies to present their lessons. The teachers’ grouping of students was problematic, and the teachers were not providing ample and varied time to students to accomplish the activities at hand. Teaches identified lack time, lack of knowledge, large class size, lack of professional support as factors hindering their practice on contextualization. Based on the findings implications were forwarded.